2023
DOI: 10.3390/molecules28041796
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Molecular Basis for Mitochondrial DNA Replication and Transcription in Health and Antiviral Drug Toxicity

Abstract: Human mitochondrial DNA (mtDNA) is a 16.9 kbp double-stranded, circular DNA, encoding subunits of the oxidative phosphorylation electron transfer chain and essential RNAs for mitochondrial protein translation. The minimal human mtDNA replisome is composed of the DNA helicase Twinkle, DNA polymerase γ, and mitochondrial single-stranded DNA-binding protein. While the mitochondrial RNA transcription is carried out by mitochondrial RNA polymerase, mitochondrial transcription factors TFAM and TFB2M, and a transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…The fully functional protein is composed of one POLG and the dimer of POLG2, encoded by the gene located on chromosome 17 [90]. The dimer enhances polymerase processivity, while the catalytic subunit additionally possesses 3 to 5 exonuclease and 5 -dRP lyase activities [91,92]. Pol γ creates a replication complex together with mitochondrial genome maintenance exonuclease 1 (MGME1), twinkle mtDNA helicase (TWNK) and the mitochondrial single-stranded DNA binding protein (mtSSB) [93].…”
Section: Discussionmentioning
confidence: 99%
“…The fully functional protein is composed of one POLG and the dimer of POLG2, encoded by the gene located on chromosome 17 [90]. The dimer enhances polymerase processivity, while the catalytic subunit additionally possesses 3 to 5 exonuclease and 5 -dRP lyase activities [91,92]. Pol γ creates a replication complex together with mitochondrial genome maintenance exonuclease 1 (MGME1), twinkle mtDNA helicase (TWNK) and the mitochondrial single-stranded DNA binding protein (mtSSB) [93].…”
Section: Discussionmentioning
confidence: 99%
“…At a structural level, this mechanism implies that DNA polymerases can exist, not only in exo and pol states, but also in multiple intermediate states. Recent structural studies on Polɣ revealed this enzyme exists in polymerase, exonuclease, as well as in an intermediate conformers 57 . Additionally Polɣ utilizes a dual checkpoint mechanism to sense nucleotide misincorporation and initiate proofreading 18 .…”
Section: A Unified Mechanism For Proofreadingmentioning
confidence: 99%
“…Mitochondrial toxicity is a well-known drawback among nucleoside analogs. Many DAA drugs used for the treatment of human immunodeficiency virus, hepatitis C or B infections, have been reported to interfere with mitochondrial DNA (mtDNA) replication and transcription, and may affect the activity of DNA polymerase γ (POLG) and mitochondrial topoisomerases [4,5]. POLG seems to be the only known DNA polymerase in animal mitochondria, and it is necessary for the transcription, replication, and maintenance of the mtDNA.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial RNA transcription and DNA replication are intertwined; both RNA transcription and DNA replication control mtDNA copy numbers. The POLG replaces the RNA polymerase and starts DNA replication from the RNA primers; perhaps POLG has a higher affinity to the transcription bubble than the RNA polymerase once RNA polymerase dissociates from the template [5]. POLG is susceptible to nucleos(t)ide analogs that treat HIV-1 infections, which contributes to mitochondrial stress and toxicity [6].…”
Section: Introductionmentioning
confidence: 99%